Using a micromechanical viscoelastic creep model to capture multi-phase deterioration in bio-based wood polymer composites exposed to moisture - Kamau-Devers, Kanotha; Miller, Sabbie A. (Construction & building materials, 2022)
•Creep in non-deteriorated (dry) and moisture-deteriorated WPCs were modelled.•Verification included capturing non-deteriorated creep data from PLA and PHBV WPCs.•Deterioration was captured through changes in mechanical and morphological data.•Deterioration model characterizing of the fiber, matrix, and interface was proposed.•Incorporating durability with mechanical performance can influence design decisions. To accurately depict in-service behavior of multi-phase, fully bio-based composites, models must be able to capture material deterioration. In this work, a viscoelastic micromechanical creep model, validated by experimental work, was proposed for bio-based wood polymer composites subject to moisture and prolonged loading. To capture the highly weakened or “deteriorated” interface incurred from fiber swelling, characterizations of the interface, fiber, and matrix were used. Experimental mechanics findings and morphological data were used to inform composite deterioration and to select modeling parameters. The model was verified using extended experimental results, and also extended to drive design of more environmentally sustainable composites.